2007
DOI: 10.7863/jum.2007.26.7.959
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of a Consecutive Cervical Pregnancy by Sonographically Guided Transvaginal Local Injection

Abstract: Conservative management of cervical pregnancy using local injection has been reported to have a low complication rate and a high efficacy for cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Ten years later, a review of the available data by Van de Meerssche et al 2 showed that only 15% of the patients required hysterectomy. Ferrara et al 10 recently reviewed 90 cases of cervical pregnancy treated conservatively using local injections and they found a surprisingly low rate (1.1%) of hysterectomy. The management depends on the clinical presentation of this condition.…”
Section: T H E R a P E U T I C S T R A T E G I E Smentioning
confidence: 97%
“…Ten years later, a review of the available data by Van de Meerssche et al 2 showed that only 15% of the patients required hysterectomy. Ferrara et al 10 recently reviewed 90 cases of cervical pregnancy treated conservatively using local injections and they found a surprisingly low rate (1.1%) of hysterectomy. The management depends on the clinical presentation of this condition.…”
Section: T H E R a P E U T I C S T R A T E G I E Smentioning
confidence: 97%
“…The most commonly reported medications are MTX and KCl. 13,21,27,35,41,44,46,51 Administration of intraamniotic prostaglandins F2α have also been described by Spitzer et al and Vega et al 59,60 Mefiprestone administered along with MTX to induce feticide has been reported by Pathak et al and Shreshta et al 43,48 In the presence of progesterone, mifepristone acts as a competitive receptor antagonist at the progesterone receptor. Mifepristone induces decidual breakdown indirectly, leading to trophoblast detachment and resulting in decreased syncytiotrophoblast production of HCG, which in turn causes decreased production of progesterone by the corpus luteum.…”
Section: Medical Therapymentioning
confidence: 90%
“…7,12 The most common risk factor is dilatation and curettage (69%), followed by previous caesarean delivery (35%). 13 Other risk factors include Asherman's syndrome, intrauterine devices, tumours and anomalies of reproductive tract. 5,14 One patient in our study had curettage and prior caesarean history.…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Most common risk factors are dilatation and curettage (70%) and cesarean section (35%) -both of which were performed previously to our presented patient [3,5]. Usual symptoms are painless vaginal bleeding (91%), followed by a period of amenorrhea, and inguinal pain (28%) [6,7].…”
Section: Discussionmentioning
confidence: 99%